Recent Progress in Protective Membranes Fabricated via Electrospinning: Advanced Materials, Biomimetic Structures, and Functional Applications - Shi, Shuo; Si, Yifan; Han, Yanting; Wu, Ting; Iqbal, Mohammad Irfan; Fei, Bin; Li, Robert K. Y.; Hu, Jinlian; Qu, Jinping (Advanced materials (Weinheim), 2022)
Electrospinning is a significant micro/nanofiber processing technology and has been rapidly developing in the past 2 decades. It has several applications, including advanced sensing, intelligent manufacturing, and high‐efficiency catalysis. Here, multifunctional protective membranes fabricated via electrospinning in terms of novel material design, construction of novel structures, and various protection requirements in different environments are reviewed. To achieve excellent comprehensive properties, such as, high water vapor transmission, high hydrostatic pressure, optimal mechanical property, and air permeability, combinations of novel materials containing nondegradable/degradable materials and functional structures inspired by nature have been investigated for decades. Currently, research is mainly focused on conventional protective membranes with multifunctional properties, such as, anti‐UV, antibacterial, and electromagnetic‐shielding functions. However, important aspects, such as, the properties of electrospun monofilaments, development of “green electrospinning solutions” with high solid content, and approaches for enhancing adhesion between hydrophilic and hydrophobic layers are not considered. Based on this systematic review, the development of electrospinning for protective membranes is discussed, the existing gaps in research are discussed, and solutions for the development of technology are proposed. This review will assist in promoting the diversified development of protective membranes and is of great significance for fabricating advanced materials for intelligent protection. Electrospinning has been used for several applications over the last 20 years. Multifunctional protective membranes in terms of novel material design, novel structure construction, and various applications via electrospinning are reviewed. Diverse protective membranes are investigated, existing problems are discussed, and solutions for future technology development are proposed. This is of significance for the sustainable development of intelligent protection systems.